2019
DOI: 10.1063/1.5115466
|View full text |Cite
|
Sign up to set email alerts
|

Thermal annealing effects in polycrystalline EuTiO3 and Eu2Ti2O7

Abstract: Using time-differential perturbed angular correlation of γ rays, we investigated the electric-field gradient of polycrystalline EuTiO3 and Eu2Ti2O7, with 181Hf(181Ta) as a probe, following different thermal treatments. The measurements were performed at ISOLDE-CERN following 80 keV implantation at the Bonn Radioisotope Separator. The experimental results indicated successful induction of different phases in the implantation recovery process at 1273 and 1373 K. These observations were combined with ab initio ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…provided in Supplementary Table 1. (10), Y = 0.50 (9), Ti = 0.00(5), B: Eu = 0.00 (10), Y = 0.00 (9), and Ti = 1.00 (5) for general formula A2B2O7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…provided in Supplementary Table 1. (10), Y = 0.50 (9), Ti = 0.00(5), B: Eu = 0.00 (10), Y = 0.00 (9), and Ti = 1.00 (5) for general formula A2B2O7.…”
Section: Discussionmentioning
confidence: 99%
“…Refinement also confirmed that the phase was perfectly ordered. The refined occupancies were Eu = 0.50 (10), Y = 0.50 (9), and Ti = 0.00(5) in site A, and Eu = 0.00 (10), Y = 0.00 (9) and Ti = 1.00 (5) in site B for the general pyrochlore formula A2B2O7.…”
Section: Structural Properties Of (Eu05y05)2ti2o7mentioning
confidence: 94%
See 1 more Smart Citation
“…By modifying the type and quantity of defects, a relatively tiny amount of dopant may significantly change the characteristics of Mn-Zn ferrites. The dynamics of grain boundary motion, phase transition temperature, pore clearance, and pore mobility are all impacted by defects [10]. In Mn-Zn ferrites of different stoichiometry, like Mn0.58Zn0.37Fe2.05-xGdxO4, Mn0.5Zn0.5ScyFe2-yO4, and Mn0.3Zn0.7Fe2-xDyxO4, the rare-earth metal substitution results in the 4f-3d coupling, which might enhance magnetic and electrical properties [3,11,12].…”
Section: Introductionmentioning
confidence: 99%